(untitled) (Economics and region, 2019)
The authors examine the role of the world currencies in the global economy and identify the main directions of further development of the world monetary system. Among the world currencies, the US dollar, euro, British pound sterling, Japanese yen and Chinese yuan are analyzed. The purpose of the paper is to investigate the role of the world currencies in the global economy and identify future trends in the development of the world financial system. The authors highlight the causes of the world currencies emergence. The basic conditions necessary for the internationalization of national currencies and the factors that influence the choice of the currency for payments under international trade agreements are outlined. The dynamics of changing the roles of the world currencies in the global economy are analyzed. The authors conclude that the behavior of the world economy when choosing an international currency in the short term is inertial. Against this background, in the absence of a deep crisis in the US economy, the US dollar will dominate the global currencies in the short term.